The imagery and abstraction trend of Chinese contemporary oil painting - Yang, Guangyu (Linguistics and Culture Review, 2021)
The relevance of the study is determined by the fact that Chinese painting is at least five thousand years old. Throughout history, Chinese artists have used light pink, gold and black colors in their work. The paper shows that sumi-e (Chinese national ink wash painting) is different from the European one. The authors show that calligraphy is inextricably linked to painting, use the same lines, materials, and tools. In China, paintings are not only artistic but also a literary style. The novelty of the study is determined by the fact that the authors of the paper highlight the aspect of the execution of oil painting without preliminary sketches. The expressiveness inherent in Chinese art is achieved through four values of the artist. It is revealed that each artist attaches great importance to the choice of their professional tools and approaches it with an increased level of responsibility. The practical significance of the study is in the fact that the paper shows the possibility of developing the culture of traditional oil painting. It is shown that two opposites must be combined at the same time: dark and light, large and small, dry and wet, short and long, rare and frequent.